2009
DOI: 10.1073/pnas.0903545106
|View full text |Cite
|
Sign up to set email alerts
|

Conserved waters mediate structural and functional activation of family A (rhodopsin-like) G protein-coupled receptors

Abstract: G protein-coupled receptors with seven transmembrane ␣-helices (GPCRs) comprise the largest receptor superfamily and are involved in detecting a wide variety of extracellular stimuli. The availability of high-resolution crystal structures of five prototypical GPCRs, bovine and squid rhodopsin, engineered A 2A-adenosine, ␤1-and ␤2-adrenergic receptors, permits comparative analysis of features common to these and likely all GPCRs. We provide an analysis of the distribution of water molecules in the transmembrane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
225
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 218 publications
(240 citation statements)
references
References 61 publications
13
225
0
1
Order By: Relevance
“…These lysines are covalently linked to the retinal chromophore. As with microbial 7TMRs, consensus clusters of buried water molecules are found in rhodopsin and ligandbinding GPCRs, consistent with the recent finding that family A GPCRs contain structurally conserved water molecules that mediate structural and functional activation (24). Relative to microbial 7TMRs, rhodopsin and ligand-binding GPCRs contain additional clusters of buried ionizable groups that correspond to the D/ERY (Asp/Glu-Arg-Tyr) motif, a conserved feature that couples GPCRs to G proteins.…”
Section: Significancesupporting
confidence: 62%
See 1 more Smart Citation
“…These lysines are covalently linked to the retinal chromophore. As with microbial 7TMRs, consensus clusters of buried water molecules are found in rhodopsin and ligandbinding GPCRs, consistent with the recent finding that family A GPCRs contain structurally conserved water molecules that mediate structural and functional activation (24). Relative to microbial 7TMRs, rhodopsin and ligand-binding GPCRs contain additional clusters of buried ionizable groups that correspond to the D/ERY (Asp/Glu-Arg-Tyr) motif, a conserved feature that couples GPCRs to G proteins.…”
Section: Significancesupporting
confidence: 62%
“…Therefore we wondered whether GPCRs also contain buried electrostatic networks that might regulate G protein activation. Indeed, several studies have highlighted the prevalence of ionizable residues, water molecules (24), and ions such as sodium (25,26) in the cores of GPCRs. Here we used pHinder to analyze a comprehensive list of 27 rhodopsin and 70 ligandbinding GPCR structures.…”
Section: Significancementioning
confidence: 99%
“…It was also suggested that a proton relay via proton wires from the retinal binding pocket to the cytoplasmic surface (as shown in figure 4.6) may occur upon receptor activation [147].…”
Section: Sequential Activation Process Of Rhodopsinmentioning
confidence: 99%
“…Thus, ordered waters function as noncovalent cofactors that actively participate in transmitting the activation signal from the retinylidene-binding pocket to the cytoplasmic face of Rho, where binding of transducin occurs. These individual waters are observed in high resolution structures of Rho as well as other G protein-coupled receptors, and a high level of conservation of polar residues in close proximity to these waters is also found in all G proteincoupled receptor sequences (9,10).…”
mentioning
confidence: 98%